THE EFFECT OF SCIENCE LITERACY ON STUDENTS' SCIENTIFIC ATTITUDES IN SCIENCE SUBJECTS IN GRADE 5 - Erni Rahmawati; Budhi Akbar (Jurnal Cakrawala Pendas, 2025)
This study aims to analyze the relationship between science literacy ability and scientific attitude of grade 5 students in science subjects at SDN Ciracas 06, East Jakarta. The sample in the study consisted of all grade 5 students of SDN Ciracas 06 East Jakarta. This study uses quantitative data analysis techniques with an inferential statistical approach, which includes correlation test, linear regression test, and linearity test. The results showed that students' science literacy skills were in the very good category with an average score of 85, while students' scientific attitudes were classified as good with an average score of 68. The correlation test showed that there was a strong positive relationship between science literacy and scientific attitudes, with a correlation value of 0.496. This indicates that the higher the student's science literacy ability, the better the scientific attitude they have. The results of the linear regression test showed that science literacy contributed 24.6% to the development of students' scientific attitudes. In addition, the linearity test shows that the relationship between these two variables is linear. The conclusion is that improving students' science literacy skills in science subjects has a positive correlation so that it is in line with improving scientific attitudes. This research has important implications for science teaching in elementary schools, especially in creating an active classroom atmosphere and supporting the development of science literacy and students' scientific attitudes. Teachers are advised to continue to apply interesting and interactive learning methods to improve both aspects. Students, as future generations, need to develop science literacy and a good scientific attitude to face technological developments. This research is expected to be the basis for further research to obtain more accurate and useful results.